Evaluation of functional outcome of displaced fracture neck of femur in elderly treated with cemented bipolar prosthesis by modified Harris hip score - Kerakkanavar, Shivakumar B.; Kaladagi, Deepak P.; Sanakal, Nagesh B.; Kaladagi, Pundaleekappa S.; Hongal, Praveenkumar A. (International Journal of Research in Orthopaedics, 2021)
Background: The current research was conducted to determine the functional outcome of the displaced fracture neck of femur in elderly patients treated with cemented bipolar hip prosthesis. Methods: The present research was a prospective study of 44 cases of displaced fracture neck of femur admitted to our institute between October 2017 and October 2019. Cases were chosen on the basis of inclusion and exclusion criteria. Cases were surgically treated with cemented bipolar hip hemiarthroplasty and functional findings were recorded with modified Harris hip score. Results: In our series of 44 cases there were 30 females and 14 males, with a maximum age of 92 years, minimum age of 65 years, and the average age was 72.72 years. At one-year follow-up, the average modified Harris hip score was 86.75% (maximum score of 95 and a minimum score of 66), overall, 20 patients (45.46%) achieved excellent, 16 patients (36.36%) achieved good, 5 patients (11.36%) achieved fair and 3 patients (6.82%) achieved poor results. 81.82% of the patients returned to the pre-fracture level of activity and independent ambulation. Patients had few complications like limb length discrepancy, 36.3% of patients had limb lengthening between 1 to 1.5 cm. Conclusions: In elderly patients with displaced neck femur fractures, cemented bipolar hip prosthesis provides good functional outcome. However further study for a longer period in a larger sample with a direct comparison between the cemented versus uncemented groups is required.